Online Sales of Unscheduled Pharmaceutical Agents: A Case Report of Tianeptine Use in the United States. Issue 5 (September 2017) - Gupta, Swapnil; Wallace, Ryan; Sloshower, Jordan
Abstract : N/A: Tianeptine is a tricyclic antidepressant that stimulates mu-opioid receptors at high doses. It is marketed and used across Europe and Latin America as an antidepressant, but is not approved by the Food and Drug Administration for use in the United States. In the United States, tianeptine is sold through online health stores as a cognition enhancer, dietary supplement, or as research chemical. We report the case of a 36-year-old man with a history of major depressive disorder, responsive to sertraline, who turned to the unmonitored use of tianeptine purchased online to treat residual feelings of apathy and boredom. His use of tianeptine was marked by rapidly escalating doses and a significant withdrawal syndrome that made discontinuation of this substance difficult. This case serves as a reminder that unscheduled pharmaceutical agents are available for misuse by the general population and have the potential to cause significant harm. Therefore, medical providers must be aware of and screen for the use of such products amongst their patients.